Navigating the Landscape of Phonology Research: A Systematic Review of Current Trends and Interdisciplinary Applications - Azzahra, Fia (Universitas Negeri Surabaya, 2025)
Phonology, a core component of linguistic study, encompasses the patterns of sounds in languages and the abstract cognitive processes that govern them. This systematic review synthesizes current trends in phonology research, aiming to provide a comprehensive overview of the discipline's evolving landscape. The review analyzed 24 studies, revealing that phonology is the predominant focus, accounting for 50% of the research, with other areas including energy studies, code review, entrepreneurship, developmental differences, visual word learning, dyslexia, and phonological awareness. Key findings include the emergence of phonological features independently of phonetic substance (Boersma, 2022), and the complexity of incomplete neutralization in Mandarin (Du & Durvasula, 2022). The integration of technology in phonological training is a significant trend, with studies showcasing the role of neural networks in phonological feature emergence (Boersma et al., 2022) and the enhancement of phonological education through digital tools (Anika, 2023). The interdisciplinary connections of phonology with other fields, such as energy studies and entrepreneurship, highlight its broad applicability and relevance. This review underscores the necessity for continued interdisciplinary research and the integration of innovative methodologies to further our understanding of phonological systems. The implications of these findings extend to educational practices, cognitive science, and technological applications, promoting a deeper understanding of phonological phenomena and encouraging future advancements in the field.